2012
DOI: 10.1158/1535-7163.mct-12-0121
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C Inhibitor AEB071 Targets Ocular Melanoma Harboring GNAQ Mutations via Effects on the PKC/Erk1/2 and PKC/NF-κB Pathways

Abstract: Somatic GNAQ mutations at codon 209 have been identified in approximately 50% of uveal melanomas (UM) and have been reported to be oncogenic through activating PLCβ-PKC-Erk1/2 pathways. We hypothesized that PKC may provide new opportunities for therapeutic targeting of UM carrying GNAQ mutations. To test this hypothesis, UM cells harboring wild type or mutant GNAQ were treated with the PKC inhibitor AEB071 (sotrastaurin) or infected with lentivirus expressing shRNAs targeting PKC isoforms. Notably, AEB071 at l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 49 publications
(68 reference statements)
5
69
0
1
Order By: Relevance
“…Only www.impactjournals.com/oncotarget a limited efficacy of LEE011 was observed and no clear evidence of increased efficacy combining it with AEB071 was detected, indicating that co-inhibition of PKC and CDK4/6 is not an optimal strategy for treating UM. The absence of increased efficacy after AEB071 + LEE011 combination could be in part explained by the fact that AEB071 decreases expression of cyclin D1 and Rb proteins and induces G1/S cell cycle arrest [16][17] [40], effects that are specific to CDK4/6 targeting.…”
Section: Discussionmentioning
confidence: 99%
“…Only www.impactjournals.com/oncotarget a limited efficacy of LEE011 was observed and no clear evidence of increased efficacy combining it with AEB071 was detected, indicating that co-inhibition of PKC and CDK4/6 is not an optimal strategy for treating UM. The absence of increased efficacy after AEB071 + LEE011 combination could be in part explained by the fact that AEB071 decreases expression of cyclin D1 and Rb proteins and induces G1/S cell cycle arrest [16][17] [40], effects that are specific to CDK4/6 targeting.…”
Section: Discussionmentioning
confidence: 99%
“…Although no treatment targets the G-protein a-subunits directly, targeted therapies directed at protein kinase C (PKC) in uveal melanoma cells harboring a GNAQ mutation inhibited the growth of uveal melanoma via PKC/Erk-1/2 and PCK/NK-kB pathways (Wu et al 2012). Another approach that has been studied in vitro is inhibition of MEK and AKT pathways; MEK inhibitor selumetinib and AKT inhibitor MK2206 decreased cell viability in a synergistic manner and may hold therapeutic promise (Ambrosini et al 2013).…”
Section: Genetic Mutations Associated With Site-specific Melanomas Uvmentioning
confidence: 99%
“…In pre-clinical studies AEB071 has been demonstrated to have at least two separate actions -suppression of autoimmunity and anti-cancer phenotypes. Studies of cancer have focused on uveal melanoma, a rare cancer that commonly has activating mutations of Gα which lead to the activation of PKC/Erk and NF-κB signal transduction, growth and survival [141]. Single agent AEB071 causes melanoma cells to undergo G1 arrest and apoptosis [141] and has synergistic effects with ionising radiation [142], with an inhibitor of PI3K α (BYL719) [143] and the MEK inhibitors PD0325901 and MEK162 [144].…”
Section: Aeb071mentioning
confidence: 99%
“…Studies of cancer have focused on uveal melanoma, a rare cancer that commonly has activating mutations of Gα which lead to the activation of PKC/Erk and NF-κB signal transduction, growth and survival [141]. Single agent AEB071 causes melanoma cells to undergo G1 arrest and apoptosis [141] and has synergistic effects with ionising radiation [142], with an inhibitor of PI3K α (BYL719) [143] and the MEK inhibitors PD0325901 and MEK162 [144]. A number of phase II studies in patients requiring immune modulation (post-organ transplant, plaque psoriasis, uveitis and ulcerative colitis) have established that AEB071 doses of 200-300 mg twice daily are well tolerated but with sufficient followup there was a lack of significant activity as an immunosuppressant [145][146][147].…”
Section: Aeb071mentioning
confidence: 99%